The impact of physical vascular therapy on biological renewal after endurance exercise within selected blood parameters. A case study - Jazdończyk, Paulina (Journal of Education, Health and Sport, 2018)
Introduction. Microcirculation functionally comprises the most important part of the human circulatory system taking place in the branched network of the smallest blood vessels. At this stage, microcirculation is responsible for transportation functions which are essential for life, namely, it carries oxygen and nutrients to tissues and removes metabolic waste products. The main objective of this study was to evaluate the effectiveness of the physical vascular therapy in the process of biological renewal after endurance exercise. Material and methods. A woman aged 61 years, weight – 82.1 kg and height – 69.8 cm. In the first and second edition, blood sampling was performed before and after endurance exercise at the same intervals for five consecutive days. The second session included physical vascular therapy for seven days before and after endurance exercise three times every day from 06.00 a.m. to 06.08 a.m., 04.00 p.m. – 04.08 p.m. in daily cycles and from 10.00 p.m. to 05.30 a.m. in night cycles.Findings 1. Physical vascular therapy applied to improve microcirculation had different effects on blood levels of sodium, potassium, calcium and magnesium in the woman and man. 2. The application of the BEMER therapy in biological renewal after endurance exercise in the woman at her sixth decade of life may be justified also as a preparation for endurance exercise.